2019
DOI: 10.3390/w11030514
|View full text |Cite
|
Sign up to set email alerts
|

Decline of Fine Suspended Sediments in the Madeira River Basin (2003–2017)

Abstract: The Madeira River is the second largest Amazon tributary, contributing up to 50% of the Amazon River’s sediment load. The Madeira has significant hydropower potential, which has started to be used by the Madeira Hydroelectric Complex (MHC), with two large dams along the middle stretch of the river. In this study, fine suspended sediment concentration (FSC) data were assessed downstream of the MHC at the Porto Velho gauging station and at the outlet of each tributary (Beni and Mamoré Rivers, upstream from the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 46 publications
0
27
1
Order By: Relevance
“…The erosion of the eastern flank of the tropical Andes provides nearly 100% of the suspended sediment load observed in the Amazon Basin (estimated between 750 and 1200 Mt/year), with a major contribution from southern Amazon rivers such as the Ucayali and Madeira. For instance, the average suspended sediment production of the Madeira River Andean catchment has recently been estimated at 640 Mt/year (Vauchel et al, 2017), but almost a third of that load is deposited in the floodplains before reaching the Amazon (Guyot et al, 2007;Armijos et al, 2013;Santini et al, 2014;Vauchel et al, 2017;Espinoza-Villar et al, 2018;Ayes-Rivera et al, 2019). Andean rivers also control the Amazon basin hydrochemistry, in particular due to the salt rocks and carbonates present in the Marañón and Ucayali basins (Moquet et al, 2011;Bouchez et al, 2017).…”
Section: Amazon-andes Connectionmentioning
confidence: 99%
“…The erosion of the eastern flank of the tropical Andes provides nearly 100% of the suspended sediment load observed in the Amazon Basin (estimated between 750 and 1200 Mt/year), with a major contribution from southern Amazon rivers such as the Ucayali and Madeira. For instance, the average suspended sediment production of the Madeira River Andean catchment has recently been estimated at 640 Mt/year (Vauchel et al, 2017), but almost a third of that load is deposited in the floodplains before reaching the Amazon (Guyot et al, 2007;Armijos et al, 2013;Santini et al, 2014;Vauchel et al, 2017;Espinoza-Villar et al, 2018;Ayes-Rivera et al, 2019). Andean rivers also control the Amazon basin hydrochemistry, in particular due to the salt rocks and carbonates present in the Marañón and Ucayali basins (Moquet et al, 2011;Bouchez et al, 2017).…”
Section: Amazon-andes Connectionmentioning
confidence: 99%
“…An analysis using environmental vulnerability indices has identified the Madeira as the Amazonian river system that is most threatened by dam construction (Latrubesse et al, 2017). Recent studies on the impacts of the Jirau and Santo Antônio dams report decreases in downstream fishery yields (Santos et al, 2018;Lima et al, 2020) and suspended sediment concentrations (Latrubesse et al, 2017)-although the attribution of suspended sediment changes to the dams has been questioned because concentrations have also decreased upstream of both reservoirs (Ayes et al, 2019). A remote sensing analysis has revealed that the area inundated by the Jirau and Santo Antônio dams is 60% larger than initially predicted in pre-dam environmental impact assessments (Cochrane et al, 2017), which may be in part related to changes in project design.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, there has been much concern regarding how the Madeira dams could affect the natural flow of sediments and associated nutrients in the Madeira River 1012 . Now, a few years after the dams were built, studies are starting to reveal decreases in downstream suspended sediment concentrations and fisheries yields 1315 . These new studies have focused on downstream impacts, but the extent to which the dam has modified upstream water chemistry and thermal structure, and how the changes affect the biota of the newly formed aquatic environments, is not known.…”
Section: Introductionmentioning
confidence: 99%